2016
DOI: 10.1371/journal.pone.0149270
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating Functional Diversity: Missing Trait Data and the Importance of Species Abundance Structure and Data Transformation

Abstract: Functional diversity (FD) is an important component of biodiversity that quantifies the difference in functional traits between organisms. However, FD studies are often limited by the availability of trait data and FD indices are sensitive to data gaps. The distribution of species abundance and trait data, and its transformation, may further affect the accuracy of indices when data is incomplete. Using an existing approach, we simulated the effects of missing trait data by gradually removing data from a plant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 36 publications
2
83
0
Order By: Relevance
“…Májeková et al . ), even in the highly intensively sampled communities that we investigated, some species might not have been observed. Although this is almost inevitable, as sampling communities truly exhaustively is generally either unfeasible or impossible, it is likely that this may have caused an underestimation of the minimum sampling effort required to reach adequate precision and accuracy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Májeková et al . ), even in the highly intensively sampled communities that we investigated, some species might not have been observed. Although this is almost inevitable, as sampling communities truly exhaustively is generally either unfeasible or impossible, it is likely that this may have caused an underestimation of the minimum sampling effort required to reach adequate precision and accuracy.…”
Section: Discussionmentioning
confidence: 89%
“…Májeková et al . (), who studied the effects of missing trait (rather than community) data on the precision of Rao's Quadratic Entropy, Functional Richness and Functional Evenness, found that the former was most robust to missing data and that the latter was least robust, suggesting that precision of the same metrics are consistently the most sensitive to any type of data deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we calculated functional trait diversity (FDIS) using the dbFD function in the R package FD (Laliberté, Legendre, Shipley, & Laliberté, ). Both plant height and SLA were log‐transformed before analysis to amplify the probability of detecting functional community patterns (Májeková et al, ). FDIS is a commonly used functional diversity metric and denotes the averaged abundance‐weighted distance between plant species to the community abundance‐weighted functional mean value.…”
Section: Methodsmentioning
confidence: 99%
“…However, the results encourage the use of a local trait dataset as the priority choice in a trait-based analysis, if one is available. Otherwise, as missing trait data should be avoided (Májeková et al, 2016), a continental trait dataset (and thus Palearctic literature)…”
Section: Consequences Of Trait Variability On Community-weighted Mementioning
confidence: 99%